Implementation of Corporate Responsibility Theories Related to The Difference in Criminal and Civil Responsibility Between Corporation and Corporate Officer - Devina Puspita Sari; Sri Ismawati; Siti Rohani; Mega Fitri Hertini; Angga Prihatin (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2023)
Corporations can be charged with criminal and civil responsibility based on corporate responsibility theories. Corporate criminal responsibility must be differentiated from the corporate officer responsibility, it’s not the same concept in civil law perspective. Corporate responsibility theories, and its implementation in court decision that talk about criminal dan civil corporate responsibility are the subject of this article. The discussion regarding implementation in criminal law perspective is based on the withdrawal of corporate criminal responsibility for the mistakes of corporate officer, even though the corporation was not prosecuted in court, on the other side, in civil law perspective, corporation can imposed based on the fault of their corporate officer even their worker by vicarious liability theory. Research was carried out using a statutory approach, a conceptual approach and a case approach. The case studies are Court Decision Nr. 20/Pdt.G/2018/PN.Jkt.Ut and Nr. 34/Pid.Sus/2019/PN.SDA. The analysis carried out that the corporate responsibility theory used in imposing criminal responsibility on a corporation can be seen in the law that regulates related criminal acts. A distinction must be made between criminal responsibility carried out by corporation and corporate officer. However, in civil law perspective, corporation can imposed based on the fault of their corporate officer even their worker by vicarious liability theory.